Menilik Efek Disruptif Penggunaan Teknologi Artificial Intelligence dalam Pembelajaran Sejarah - Silvy Mei Pradita; Didin Saripudin; Leli Yulifar; Erlina Wiyanarti (Universitas Hamzanwadi, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to the educational paradigm, including history learning, which is now shifting from a conventional model to a more adaptive and interactive digital system. This study aims to analyze the positive impacts and disruptive effects of AI implementation in history education while formulating mitigation strategies to balance technological advancement with humanistic values. Using a literature study method and a descriptive-analytical approach, the findings indicate that AI has the potential to enrich history learning through personalized learning, digital visualization based on VR and AR, and data analytics that assist teachers in understanding students’ needs more deeply. However, challenges arise in the form of shifting teacher roles, dependency on algorithmic systems, and ethical as well as privacy concerns. Therefore, strategies such as strengthening teachers’ digital literacy, implementing hybrid learning models that integrate AI with human interaction, and establishing ethical policies focusing on students’ rights protection are essential. Thus, the application of AI should be positioned as a means to reinforce the humanistic dimension and reflective character of learners, rather than merely serving as a tool for learning efficiency in the digital era.